Study treating infected pigeons with Newcastle virus and effects on the mortality rate - Dakhil, Huda Ghanim; Abbas, Mariam Mustafa (Journal of agricultural, environmental and veterinary sciences, 2020)
Newcastle virus is a dangerous infectious virus that causes economic losses in birds such as pigeons, chickens and others. The current study was aimed to treat Newcastle disease in pigeons and record effects of it on treated pigeon embryos for several generations. Extracted the clotted blood from the neck of infected birds by a sterile needle, supplying their diet with the garlic and orange juice, and feeding them by-hand for 1-2 weeks. The current study recorded the recovery of all treated birds under the study. They were exhibiting less twisting of the head, back to eat by themselves, and the eggs were laid after 8-10 weeks after treatment. It was observed that only female pigeons infected with virus during the study period from September 2019 to April 2020. The treated pigeons laid several generations. The mortality was 50%, 100%, 100%, and 50% for the first, second, third, and fourth-generation respectively. It was observed some behavioral changes in 2 of chicks from the healthy chick pigeons of the first generation, while in the fourth generation, was noticed that 5 of chicks were infected immediately after hatching and they died at an age of 5-7 days. The current study concluded that removing the clot with diet played effective role in treating infected pigeons, also the Newcastle disease caused a mortality of 75% in embryos of treated pigeons. This study recommends to great caution when removing the blood clot, the infected chicks must be isolated.